Occurrence of Esophageal Atresia With Tracheoesophageal Fistula in Siblings From Three-Generation Family Affected by Variable Expressivity MYCN Mutation: A Case Report - Klaniewska, Magdalena; Toczewski, Krystian; Rozensztrauch, Anna; Bloch, Michal; Dzielendziak, Agata; Gasperowicz, Piotr; Slezak, Ryszard; Ploski, Rafał; Rydzanicz, Małgorzata; Smigiel, Robert; Patkowski, Dariusz (Frontiers in Pediatrics, 2021)
The MYCN oncogene encodes a transcription factor belonging to the MYC family. It is primarily expressed in normal developing embryos and is thought to be critical in brain and other neural development. Loss-of-function variants resulting in haploinsufficiency of MYCN, which encodes a protein with a basic helix-loop-helix domain caused Feingold syndrome (OMIM 164280, ORPHA 391641). We present occurrence of esophageal atresia (EA) with tracheoesophageal fistula in siblings from three-generation family affected by variable expressivity of MYCN mutation p.(Ser90GlnfsTer176) as a diagnostic effect of searching the reason of familial esophageal atresia using NGS-based whole exome sequencing (WES). All of our affected patients from presented family showed microcephaly and toe syndactyly which was also frequent in literature. Just one of them had clinodactyly. No one had brachymesophalangy and hypoplastic thumbs. The latest report noted that patients with EA and Feingold syndrome were also those with the more complex and severe phenotype. However, following a thorough review of the present literature, the same association was not found, which is also confirmed by the case we described. The variable phenotypic expression of the patients we described, as well as data from the literature, guide a careful differential diagnosis of Feingold syndrome even in cases of poorly expressed and nonspecific symptoms.